THE INFLUENCE OF SCALING AND ROOT PLANING ON THE GLICEMIC STATUS IN PATIENTS WITH DIABETES MELLITUS TYPE II - Liliana Pasarin; Irina Ursarescu-Sufaru; Ioana Mârțu; Sorina Solomon; Alexandra Martu-Stefanache; Arina Ciocan-Pendefunda; Silvia Martu (Romanian Society of Oral Rehabilitation, 2017)
The study proposes an assessment of the influence of the periodontal disease therapy by scaling and root planing on the glicemic status in patients with type II diabetes mellitus. Materials and method: The study was conducted on 21 patients with type I diabetes mellitus (study group) and 10 systemically healthy subjects (control group). We examined: the degree of glycemic control (by measuring the glycated hemoglobin), the periodontal and oral hygiene parameters at the baseline and after 4 weeks, 6 months and 12 months after the periodontal treatment which consisted in scaling and root planning. Results and discussion: The subjects with a poor glycemic control presented a higher percentage of sites with attachment loss, significantly higher amounts of bacterial plaque, sub-gingival calculus and gingival bleeding when compared with the control group or the subjects with good or moderated glycemic control. In the same group we observed a rapid recurrence of the deep periodontal pockets after 12 months. Conclusions: The prolonged poor control of the glycemia and the time elapsed from the debut of the diabetes were closely related with its complications. The comparisons between the diabetes and the control groups demonstrated that diabetes mellitus is a risk factor for the periodontal disease.